Validation of French versions of the 15-item picker patient experience questionnaire for adults, teenagers, and children inpatients - Clement P. Buclin; Clement P. Buclin; Adriana Uribe; Justine E. Daverio; Justine E. Daverio; Arnaud Iseli; Johan N. Siebert; Johan N. Siebert; Guy Haller; Guy Haller; Stéphane Cullati; Stéphane Cullati; et al. (Frontiers in Public Health, 2024)
ObjectivesNo French validated concise scales are available for measuring the experience of inpatients in pediatrics. This study aims to adapt the adult PPE-15 to a pediatric population, and translating it in French, as well as to establish reference values for adults, teenagers, and parents of young children.MethodsCultural adaptation involved forward and backward translations, along with pretests in all three populations. Dimensional structure and internal consistency were assessed using principal component analysis, exploratory factor analysis, and Cronbach's alpha. Construct validity was assessed by examining established associations between patient satisfaction and inpatient variables, including length of stay, and preventable readmission.ResultsA total of 25,626 adults, 293 teenagers and 1,640 parents of young children completed the French questionnaires. Factor analysis supported a single dimension (Cronbach's alpha: adults: 0.85, teenagers: 0.82, parents: 0.80). Construct validity showed the expected pattern of association, with dissatisfaction correlating with patient- and stay-related factors, notably length of stay, and readmission.ConclusionThe French versions of the PPE-15 for adults, teenagers and parents of pediatric patients stand as valid and reliable instruments for gauging patient satisfaction regarding their hospital stay after discharge.